Reciprocal modulation of Cav2.3 voltage‐gated calcium channels by copper(II) ions and kainic acid. Issue 3 (30th August 2018) - Neumaier, Felix; Akhtar‐Schäfer, Isha; Lüke, Jan Niklas; Dibué‐Adjei, Maxine; Hescheler, Jürgen; Schneider, Toni
Abstract: Kainic acid (KA) is a potent agonist at non‐N‐methyl‐D‐aspartate (non‐NMDA) ionotropic glutamate receptors and commonly used to induce seizures and excitotoxicity in animal models of human temporal lobe epilepsy. Among other factors, Cav 2.3 voltage‐gated calcium channels have been implicated in the pathogenesis of KA‐induced seizures. At physiologically relevant concentrations, endogenous trace metal ions (Cu 2+, Zn 2+ ) occupy an allosteric binding site on the domain I gating module of these channels and interfere with voltage‐dependent gating. Using whole‐cell patch‐clamp recordings in human embryonic kidney (HEK‐293) cells stably transfected with human Cav 2.3d and β3 ‐subunits, we identified a novel, glutamate receptor‐independent mechanism by which KA can potently sensitize these channels. Our findings demonstrate that KA releases these channels from the tonic inhibition exerted by low nanomolar concentrations of Cu 2+ and produces a hyperpolarizing shift in channel voltage‐dependence by about 10 mV, thereby reconciling the effects of Cu 2+ chelation with tricine. When tricine was used as a surrogate to study the receptor‐independent action of KA in electroretinographic recordings from the isolated bovine retina, it selectively suppressed a late b‐wave component, which we have previously shown to be enhanced by genetic or pharmacological ablation of Cav 2.3 channels. Although the pathophysiological relevance remains to be firmly established, we speculate that reversal of Cu 2+ ‐induced allosteric suppression, presumably via formation of stable kainate‐Cu 2+ complexes, could contribute to the receptor‐mediated excitatory effects of KA. In addition, we discuss experimental implications for the use of KA in vitro, with particular emphasis on the seemingly high incidence of trace metal contamination in common physiological solutions. Abstract : Kainic acid (KA) is a potent, non‐degradable agonist at non‐NMDA ionotropic glutamate receptors (iGluRs) and commonly used for induction of experimental seizures. Here, we describe a iGluR‐independent mechanism of KA effects on Cav 2.3 voltage‐gated Ca 2+ channels, which involves reversal of tonic Cu 2+ suppression, presumably through formation of kainate‐Cu 2+ complexes. (left part of the cartoon). These effects could sensitize Cav 2.3 channels to the KA‐induced (iGluR‐dependent) membrane depolarization (right part of the cartoon), thereby contributing to hyperexcitation and excessive Ca 2+ ‐influx.